Analysis of renal blood flow and renal volume in normal fetuses and in fetuses with a solitary functioning kidney. (21st November 2017) - Hindryckx, An; Raaijmakers, Anke; Levtchenko, Elena; Allegaert, Karel; De Catte, Luc
Abstract: Objective: To evaluate renal blood flow and renal volume for the prediction of postnatal renal function in fetuses with solitary functioning kidney (SFK). Methods: Seventy‐four SFK fetuses (unilateral renal agenesis [12], multicystic dysplastic kidney [36], and severe renal dysplasia [26]) were compared with 58 healthy fetuses. Peak systolic velocity (PSV), pulsatility index (PI), and resistance index (RI) of the renal artery (RA) were measured; 2D and 3D (VOCAL) volumes were calculated. Renal length and glomerular filtration rate (GFR) were obtained in SFK children (2 years). Results: Compared with the control group, the PSV RA was significantly lower in nonfunctioning kidneys and significantly higher in SFK. Volume measurements indicated a significantly larger volume of SFK compared with healthy kidneys. All but 4 children had GFR above 70 mL/min/1.73 m 2, and compensatory hypertrophy was present in 69% at 2 years. PSV RA and SFK volume correlated with postnatal renal hypertrophy. No correlation between prenatal and postnatal SFK volume and GFR at 2 years was demonstrated. Conclusion: Low PSV RA might have a predictive value for diagnosing a nonfunctioning kidney in fetuses with a SFK. We demonstrated a higher PSV RA and larger renal volume in the SFK compared with healthy kidneys. Abstract : What's already known about this topic? There are limited data on Doppler studies of the renal arteries in case of renal anomalies. Compensatory hypertrophy is a physiological adaptation to the presence of only 1 functional kidney and can be demonstrated in prenatal period. What does this study add? We demonstrated the predictive value of the peak systolic velocity in the renal artery (PSV RA) for diagnosing a nonfunctioning kidney. We also demonstrated a higher PSV RA value and larger renal volume in the solitary functioning kidney (SFK) compared with kidneys of healthy fetuses.